2015
DOI: 10.18538/lthe.v12.n2.186
|View full text |Cite
|
Sign up to set email alerts
|

The effect of online collaborative project-based learning on English as a Foreign Language learners' language performance and attitudes

Abstract: The present study investigated the effect of online collaborative project-based learning on the language performance and attitudes of intermediate level students at the College of Applied Sciences in Oman. The study is a quasi-experimental study and the sample consisted of four classes (93 students in total) in Nizwa College of Applied Sciences. These participants were in their foundation year and were taking the Academic English Course during the time of the research experiment. Two classes were assigned to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 9 publications
1
12
0
Order By: Relevance
“…Collaborative, knowledge outcome, skill outcome [24]. Collaborative, experimental group, control group [25].…”
Section: Collaborationmentioning
confidence: 99%
See 1 more Smart Citation
“…Collaborative, knowledge outcome, skill outcome [24]. Collaborative, experimental group, control group [25].…”
Section: Collaborationmentioning
confidence: 99%
“…Increased knowledge and abilities obtained generate good feedback when teachers and students collaborate [24]. Both the experimental group and control group examined the act of student learning in a group of people that worked together [25]. Table 1 shows the research construct and prior research variables findings of the many scholars in collaboration.…”
Section: Collaborationmentioning
confidence: 99%
“…The study of project-based online collaborative learning strategies already has the results of research. Project-based collaborative learning is considered a useful method to enhance active, meaningful, and directed communication among students in which its learning can enhance English language skills, particularly writing skills provided students try to collaborate (Al Rawahi & Al-Mekhlafi, 2015). Another study concluded that project-based online collaborative learning uses ADDIE Model to get positive feedback (Nadiyah & Faaizah, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In addition to communication skills, technical skills need to be mastered in implementing online learning in the early stages of learning (Almekhlafy, 2021;Eynon & Malmberg, 2020). The problems students encounter throughout online collaborative learning could be the causality for the lack of learning effectiveness (Al-Rawahi & Al-Mekhlafi, 2015;Sadiq Rabab'h & Veloo, 2015). Thus, Lei and Medwell (2021), Sumuer (2018) and Lee et al (2014) suggested that students receive exposure and technical training at the commencement of the learning period.…”
Section: Study Discussionmentioning
confidence: 99%